Investigating sexual assault cases - Chancellor, Arthur S. (CRC Press, 2022)
"Investigating Sexual Assault Cases, Second Edition serves as an essential textbook for courses in investigating rape and sexual assault. As with the first edition, this second edition includes the latest research and techniques in coverage of victimology, offender typology, investigative techniques, interviewing, and legal implications. This new, second edition includes chapters on child victims and molestation, sexual homicides as potentially staged events, grooming, interviewing techniques, and same-sex, elder, and special populations as victims of sexual assault. The book fills a current void in the body of literature on the topics of rape and sex crime investigation. Many previous writings, while informative, do not address all the investigative processes necessary for an investigation to be thorough and complete. By providing a fresh approach to the topic, the author aims to augment those writings and, ultimately, improving the reader' awareness by being much more attuned to the needs of-and taking investigative cures from-the victim. Key Features: Outlines the complete investigative process for sexual assault cases, from evidence collection and interviews to court and legal proceedings Addresses victims and victimology, offender typology, the importance of the investigative interviewing process, and working with attorneys Includes new chapters on grooming, sexual homicides, SAFE examinations, and child-specific interviewing techniques Added coverage looks at same-sex crimes, crimes against men, elder victims, and assault of vulnerable populations In addition to being used in coursework in Forensic Science and Criminal justice programs, Investigating Sexual Assault Cases, Second Edition will serve as an essential reference for police detectives, criminal and death investigators, legal professionals, sexual assault nurses, and those who provide health, and mental health, services to populations experiencing sexual assault"--